Solar panels cleaning robot - Ling, Xin Wei (2023)
The project aims to develop a solar panel cleaning robot that can clean a rooftop with over 100 solar panels arranged in an array. The accumulation of dust and debris on solar panels can significantly reduce their efficiency and decrease energy output. There are two types of solar panel cleaning robots in the market, namely the robot moving directly on the solar panels and the railguided robot. However, the first type is not suitable for solar panels arranged in multiple arrays with gaps, and the second type requires infrastructure expenses. This project introduces a solar panel cleaning robot with a moving frame and a cleaning robot that can move on the frame to clean the panels. This design avoids the weight of the robot on the surface of the solar panels and solves the gaps issue. The robot can remove stubborn dirt, such as bird droppings, and improve the efficiency and energy output of the solar panels, which is essential for meeting the increasing demand for renewable energy.